ANALISIS PEMBELAJARAN IPAS BERBASIS KEARIFAN LOKAL DALAM PENGUATAN KARAKTER SISWA SEKOLAH DASAR - M. Ihsan Ramadhani (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze science and social studies (IPAS) learning based on local wisdom in strengthening elementary school students’ character. The research uses a qualitative method with a case study approach through observation, interviews, and documentation. The results show that IPAS learning integrated with local wisdom helps students understand the material more easily because it is related to their surrounding environment. In addition, this learning approach fosters character values such as cooperation, responsibility, and environmental awareness. However, there are still challenges such as limited learning media and teacher innovation. In conclusion, local wisdom-based IPAS learning is effective in strengthening students’ character in a contextual and meaningful way.